Association between Gingival Thickness and Recession in Nonperiodontitis Patients - Marjita Sarma; Nina Shenoy (Wolters Kluwer Medknow Publications, 2021)
Introduction: Gingival biotype defined as a genetically determined trait describes the thickness of gingiva faciopalatally. Gingival thickness plays an important role in the development and successful treatment of mucogingival defects. Gingival recession (GR) is an undesirable condition that creates root exposure, sensitivity, and unesthetic appearance. One of the main causes proposed for GR is an overzealous toothbrushing habit. Gingival tissues can be considered as "picture framework" for restorative and aesthetic procedures. The restorative dentist must take into account the response of gingival tissues to both inflammation and restorative margins to achieve maximum desirable outcomes. Hence, the aim of this study was to determine the association between gingival thickness (GT) and GR in nonperiodontitis patients. Materials and methods: The cross-sectional study was conducted in the Department of Periodontology, Mangalore. Eighty subjects with GR of both genders aged 18 to 35 years participated in the study. GT was assessed in the maxillary and mandibular teeth using the probe transparency method. A questionnaire was utilized to determine the toothbrushing habits of the subjects. Results: Thin gingiva was more commonly found in the maxillary arch (50%) and anterior sextant (52.50%). Maxillary posterior teeth were found to be frequently affected with GR (4.49%). Comparison of GT in the anterior and posterior sextants was not statistically significant (P = 0.43). A higher prevalence of thin biotype (73.8%) was found in sites with recession. Chi-squared test was used to determine the association between GT and GR. Statistical analysis was performed using the SPSS software version 22 (IBM). Conclusion: It can be concluded that there were variations in GT with respect to dental arch and sextants. Gingiva was thinner in the maxillary arch and anterior sextant. Receded surfaces were considerably higher on the buccal surfaces of posterior teeth. Higher prevalence of thin biotype was found at sites with recession. Subjects with splaying or flattening of their toothbrush bristles had a higher mean recession depth when compared with other subjects. However, the association between GT and GR was not statistically significant.